2018
DOI: 10.21521/mw.6047
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adiponectin levels and some metabolic parameters in dairy cows with subclinical and clinical ketosis

Abstract: The aim of the presented study was to evaluate the relationship between adiponectin and non-esterified fatty acids (NEFA), β-hydroxybutyric acid (BHBA), glucose, albumin, Gamma-Glutamyl Transferase (GGT), calcium, phosphorus and Blood Urea Nitrogen (BUN) levels in healthy cows and cows suffering clinical or subclinical ketosis in the early postpartum period. A total of 45 Holstein-Fresian dairy cows, consisting of 15 with clinical ketosis, 15 with subclinical ketosis and 15 healthy controls, was used in the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
0
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
2
0
0
2
Order By: Relevance
“…To further verify this speculation, subclinical ketosis characterized blood parameters at the sampling time points were analyzed. Significantly higher concentrations of NEFA and BHBA and the concurrent significantly lower blood triacylglycerol as well as the lower blood glucose trend in the RS group when compared with the CS group were indicative of a negative energy balance and liver metabolic disorder, which were consistent with other studies . Even though the concentration of different blood parameters did not go over or below the current subclinical diagnosis threshold, the comparison showed expectable evaluative standards and potential risk .…”
Section: Discussionsupporting
confidence: 87%
“…To further verify this speculation, subclinical ketosis characterized blood parameters at the sampling time points were analyzed. Significantly higher concentrations of NEFA and BHBA and the concurrent significantly lower blood triacylglycerol as well as the lower blood glucose trend in the RS group when compared with the CS group were indicative of a negative energy balance and liver metabolic disorder, which were consistent with other studies . Even though the concentration of different blood parameters did not go over or below the current subclinical diagnosis threshold, the comparison showed expectable evaluative standards and potential risk .…”
Section: Discussionsupporting
confidence: 87%
“…Research, including studies on 3T3-L1 cells, has demonstrated that adiponectin release declines when lipolysis is stimulated by β-adrenergic substances [53]. Consistent with findings from Akgul et al [54] and Mann et al [55], cows that exhibited hyperketonemia after calving had diminished adiponectin levels. Furthermore, Kabara et al [56] found that adiponectin exposure notably lowered TNF-α levels in monocytes activated by LPS, thus significantly diminishing their inflammatory activity.…”
Section: Discussionsupporting
confidence: 62%
“…Süt sığırlarında yüksek kan NEFA ve BHBA seviyeleri negatif enerji balansının temel göstergeleridir. Bir sürünün ketozis, karaciğer yağlanması ve NED durumunu değerlendirmek için metabolik profil testinde NEFA, BHBA, glikoz, albümin, GGT ve BUN düzeylerinin dikkate alınması gerektiği bildirilmiştir (2). Çalışma gruplarımız arasında Grup-1'in glikoz (p<0,001) ve albümin (p<0,01) düzeylerinin Grup-2'den anlamlı derecede düşük, GGT (p<0,001), AST (p<0,05) ve kalsiyum (p<0,01) düzeylerinin ise anlamlı derecede yüksek olduğu tespit edildi (Tablo 1).…”
Section: Tartışma Ve Sonuçunclassified
“…BHBA dolaşımdaki dominant keton cismidir ve tüm vücutta, plazmada veya serumda nispeten stabil olarak bulunmaktadır (10,11,15,25). Ketozisin tanısı kan BHBA düzeyine dayanmaktadır (2). Süt ineklerinde ketozisin tanısı için farklı BHBA eşik değerleri kullanılmaktadır (12,18,25).…”
Section: Tartışma Ve Sonuçunclassified